2012
DOI: 10.1002/ijc.27961
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of cancer stem cells

Abstract: Heterogeneity of tumor tissue has been accounted for in recent years by a hierarchy-based model in which cancer stem cells (CSCs) have the ability both to self-renew and to give rise to differentiated tumor cells and are responsible for the overall organization of a tumor. Research into CSCs has progressed rapidly and concomitantly with recent advances in the biology of normal tissue stem cells, resulting in the identification of CSCs in a wide range of human tumors. Studies of mouse models of human cancer hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 82 publications
(172 reference statements)
1
98
0
Order By: Relevance
“…For this reason, glioblastomas almost always relapse, highlighting the need for more precisely targeted therapeutic approaches. A number of recent studies have demonstrated that tumors are composed of cells with functional heterogeneity that form a hierarchy, especially in the context of tumor initiation (3,4). Characterized by its heterogeneous tumor types (5)(6)(7)(8), glioblastoma is now also thought to be initiated and maintained by a subpopulation of tumor cells, called brain tumor stem cells or brain tumor-initiating cells (BTIC; refs.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, glioblastomas almost always relapse, highlighting the need for more precisely targeted therapeutic approaches. A number of recent studies have demonstrated that tumors are composed of cells with functional heterogeneity that form a hierarchy, especially in the context of tumor initiation (3,4). Characterized by its heterogeneous tumor types (5)(6)(7)(8), glioblastoma is now also thought to be initiated and maintained by a subpopulation of tumor cells, called brain tumor stem cells or brain tumor-initiating cells (BTIC; refs.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of cancer stem cells was originally introduced in hematological malignancies and further extended to solid cancers such as breast cancer and brain tumors. (97) Cancer stem cells have been characterized by their self-renewal potential, multidirectional differentiation potential, and niche dependence, similar to other stem cells, in addition to their highly tumorigenic potential. Furthermore, cancer stem cells have been known for their resistance to conventional chemotherapy or radiotherapy; therefore, they may be an emerging target for drug development.…”
Section: Evaluation Of Oncology Drugs Based On New Conceptsmentioning
confidence: 99%
“…In additional, the cancer stem cell theory has been proposed [38,49,50] . Cancer stem cells (CSCs) are a subpopulation of tumor cells that have the capacity to self-renew, provide life-long cell growth and produce distinct cell clones [49][50][51] . The detailed analysis of properties and methods of isolation of CSCs has been presented in a series of reviews.…”
Section: Modern Biochemistry and Post-genomic Technologies In Researcmentioning
confidence: 99%